Assessment of acute pain in cats: signs, tools and limitations - L White, Kate (Wiley, 2017)
Recent advances in pain assessment in companion animals represent a tenacious, painstaking and time-consuming dedication to improving animal welfare. Attitudes and knowledge about pain assessment, particularly in cats, have changed dramatically in the past few decades, representing a very obvious shift to prioritising analgesia, which is important from an ethical and humane standpoint. Time for training and practising pain assessment must be created in the veterinary team, to ensure consistency for intervention and improving practice. Adopting pain assessment as one of the ‘vital signs’ in the hospitalised patient evaluation is a progressive and necessary step. Discussing pain assessment with cat owners, and providing resources about pain assessment, will optimise welfare, strengthen the human-animal bond and ultimately improve the client-practice relationship and reputation.